The Activity of Tadas Daugirdas in Warsaw (1877–1891): From a Painter to an Archaeologist - Raila, Eligijus (Lietuvos istorijos studijos, 2022)
Tadas Daugirdas actively participated in the National revival culture but later was forgotten. His work covered several areas of cultural and intellectual life including painting, archaeology, ethnology, museology, and publicist writing. Daugirdas contributed significantly to the creation of the national flag of Lithuania. The fourteen years, from 1877 to 1891, he spent in Warsaw had the great influence on his worldview. Living in Warsaw he maintained close relationship with such people as artist and art critic Stanisław Witkiewicz, doctor and ethnologist Władysław Matlakowski, archaeologists Adam Honory Kirkor, Dmitrij Samokvasov, and Gotfryd Ossowski; he also corresponded with Mečislovas Davainis-Silvestraitis on the issues of Lithuanianism. The Warsaw period determined his future activities which he developed after his return to Lithuania. He came to Warsaw as a painter and returned to his parents’ manor in Lithuania as an archaeologist and a promoter of folk art.
Keywords: Tadas Daugirdas; Warsaw; positivism; fine arts; archaeology; folk art